BODIPY‐Pyrene and Perylene Dyads as Heavy‐Atom‐Free Singlet Oxygen Sensitizers. Issue 7 (23rd March 2018) - Filatov, Mikhail A.; Karuthedath, Safakath; Polestshuk, Pavel M.; Callaghan, Susan; Flanagan, Keith J.; Wiesner, Thomas; Laquai, Frédéric; Senge, Mathias O.
Abstract: Dyads combining BODIPY as an electron acceptor and pyrene or perylene as electron donor subunits were prepared and their photophysical properties were studied by steady‐state and transient spectroscopy. Depending on the structure of the subunits and the polarity of the media, the dyads show either bright fluorescence or photo‐induced electron transfer (PeT) in solution. Charge‐transfer (CT) states formed as a result of PeT and were found to yield triplet excited states of the BODIPY. In the presence of molecular oxygen, the dyads sensitize singlet oxygen ( 1 O2 ) with quantum yields of up to 0.75. Abstract : Against the grain : Efficient intersystem crossing (ISC) in BODIPY electron‐donor/acceptor dyads is reported. Unlike conventional chromophores in which triplet state formation relies on heavy atoms and is predetermined by the chemical structure of the molecule, fluorescence and ISC in the studied dyads can be adjusted by the polarity of the media.